2011
DOI: 10.1111/j.1460-9568.2011.07877.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus‐induced dissociation of neuronal firing rates and local field potential gamma power and its relationship to the blood oxygen level‐dependent signal in macaque primary visual cortex

Abstract: The functional magnetic resonance imaging (fMRI) blood oxygenation level-dependent (BOLD) signal is regularly used to assign neuronal activity to cognitive function. Recent analyses have shown that the local field potential (LFP) gamma power is a better predictor of the fMRI BOLD signal than spiking activity. However, LFP gamma power and spiking activity are usually correlated, clouding the analysis of the neural basis of the BOLD signal. We show that changes in LFP gamma power and spiking activity in the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 61 publications
11
59
0
Order By: Relevance
“…Miller and colleagues suggest that principal component decomposition of the signal would reveal far higher alpha power in the baseline condition (Miller et al, 2009b). In line with this observation, others have shown an increase in low frequency oscillations during baseline in V1 using human brain mapping (Bartolo et al, 2011;Miller et al, 2010) and animal single unit recordings (Okun et al, 2010). Variations in alpha power during baseline recording in V1, unlike in IPS, are not correlated between nearby electrodes, implicating that the same local process generates alpha oscillations during surround stimulation.…”
Section: Role Of Alpha Oscillations In Resting and Suppressionmentioning
confidence: 71%
“…Miller and colleagues suggest that principal component decomposition of the signal would reveal far higher alpha power in the baseline condition (Miller et al, 2009b). In line with this observation, others have shown an increase in low frequency oscillations during baseline in V1 using human brain mapping (Bartolo et al, 2011;Miller et al, 2010) and animal single unit recordings (Okun et al, 2010). Variations in alpha power during baseline recording in V1, unlike in IPS, are not correlated between nearby electrodes, implicating that the same local process generates alpha oscillations during surround stimulation.…”
Section: Role Of Alpha Oscillations In Resting and Suppressionmentioning
confidence: 71%
“…Several investigators have shown that this narrowband peak is present for simple grating stimuli but not for other similar stimuli. For example, the peak is reduced or eliminated by the introduction of a second grating [32, 33] or superimposed white noise [34] and is absent for low to moderate stimulus contrasts [35]. Importantly, a broadband spectral elevation has been shown in several of these stimulus configurations which eliminate the narrowband gamma peak [33, 35].…”
Section: Discussionmentioning
confidence: 99%
“…We are not alone in this negative result. While stimulus-related gamma-band effects have often been reported, such effects are highly sensitive to experimental parameters such as the exact size, orientation, and spectral content of the visual stimulus (Bartolo et al 2011;Berens et al 2008;Gieselmann and Thiele 2008;Hermes et al 2014;Jia et al 2011;Lima et al 2010). Our visual stimuli were chosen to best drive the spiking response of the population as a whole without concern for gamma-band effects and therefore might not have triggered an increase in gammaband SFC or induced gamma amplitude.…”
Section: Discussionmentioning
confidence: 99%